Moral Decadence Among Students: A Social Analysis of Changes in Values and Norms at Muhammadiyah 06 Medan Middle School - Husin, Husin; Tumiran, Tumiran (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This research aims to explore the phenomenon of declining moral values among students at Muhammadiyah 06 Junior High School in Medan through the perspective of Islamic education. The investigation addresses the pressing issue arising from globalization and rapid technological advancement, which introduce external values that often conflict with local cultural and religious principles. In this context, adolescents in the formative stage of identity development become particularly susceptible to behaviors that deviate from moral and ethical norms. Methodology: A qualitative descriptive-analytical approach was employed. The subjects consisted of students, teachers, homeroom teachers, and the principal, all directly involved in the learning process and behavior supervision. Data were collected through observation, in-depth interviews, and documentation, including school rules and student violation records. Data were analyzed using Miles and Huberman’s interactive model of reduction, presentation, and conclusion, with validity ensured through source and method triangulation. Main Findings: The study identified two major findings. First, moral decline is evident in disrespect toward teachers, increased bullying, academic dishonesty, and misuse of social media, which reflects Durkheim’s concept of anomie. Second, Islamic education functions as a moral bulwark through congregational prayer, Qur’anic recitation, moral lessons, and teacher role modeling. These practices enhance students’ self-control and spiritual awareness, supported by QS. Al-‘Ankabut (29:45). Novelty/Originality of this study: The study demonstrates that synergy between religious education, teacher exemplarity, and parental involvement is an effective model for preventing adolescent moral decline while strengthening Islamic identity in the era of globalization.